Condiciones de las empresas hoteleras de la categoría tres estrellas del centro histórico de Trujillo, para prestar un servicio de calidad bajo el enfoque servqual y lograr la satisfacción del cliente. - Lavado Jara, Armando Alex (2013)
The present review of tourism research called "Conditions of the hotel companies of the category three stars of the historic centre of Trujillo, to provide a service of quality under the SERVQUAL approach and achieve customer satisfaction", aims to determine the conditions that the hotel companies are taking to meet the expectations of its customers, in terms of their perceptions; using the SERVQUAL method for this, which will help to determine the most representative points that these hotels have, in order to achieve customer satisfaction, providing a quality service, from the first moment in which the guest has perceive the service, since the quality of a service is subjective, and is directly related to what the customer perceivesive, the judgment on the service provided._x000D_ Conditions presenting hotels three stars in the historical center of Trujillo, in relation to its tangible elements of infrastructure and equipment, it has been concluded that 6 of the 11 hotels are complying with the rules laid down in the existing regulation; In addition, they present visually appealing physical facilities; equipment look modern and sophisticated, thus achieving simplicity and speed in the service provided to guests; and a team that shows at all times clean, what marks the difference between such establishments. And finally, you have to the: reliability; determined by the ability to deliver the product promised to the guest; these variables are key elements to provide a quality service._x000D_ On the other hand, as 60% of the human capital that is located in the hotels three stars in the historical center of Trujillo, considers that the customer is key for the path and positioning of the hotel where they work; and to individual guest attention and thus the optimal connection with them, they are situations indispensable to achieve the satisfaction of customers._x000D_ And finally; 11 Hotels three stars of the historic Center of Trujillo, only 7 have demonstrated a reliability in its hotel product, indicating that if they can provide a quality service under the SERVQUAL approach, by the fact that have filed properly service the first time, avoiding errors, and the discomfort of the host, in addition, they have gained the trust and loyalty of the whole organization of the hotel guests which indicates the execution of promised service, and by the fact that maintain a clear organizational culture, in relation to the importance of the customer is to the hotel company.